2018
DOI: 10.1108/ejm-03-2016-0188
|View full text |Cite
|
Sign up to set email alerts
|

To stay or switch: breaking the habit of status quo through imagery perspective

Abstract: Purpose When consumers imagine themselves in various consumption scenarios, they can do so from the actor or the observer perspective. These different vantage points are known as imagery perspectives. This paper aims to investigate how imagery perspectives can influence consumers’ decisions to stay with the status quo (default option) or to switch to an alternative. Design/methodology/approach A series of four experimental design studies were conducted in both lab and online settings to study consumers’ swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
0
16
0
2
Order By: Relevance
“…Ghazali (2011) and Ghazali et al (2011) indicated that habits, or inertia, in the context of online purchasing, were "mindless" actions evolving from multiple "reasoned" or "mindful" actions in the past. Saine et al (2018) used the term "habitual inertia", suggesting it results from overvaluation of sunk costs, cognitive miserliness, and the inclination to maintaining control through constancy. Meanwhile, Jolley et al (2006) considered satisfaction with earlier behaviour to influence habitual behaviour, Status-quo satisfaction and smartwatch adoption reinforcing inertia (Nel and Boshoff, 2019); thus, habits were considered conceptually different from inertia.…”
Section: Literature Review 21 Diffusion Of Innovation Inertia and Resistance To Innovationmentioning
confidence: 99%
“…Ghazali (2011) and Ghazali et al (2011) indicated that habits, or inertia, in the context of online purchasing, were "mindless" actions evolving from multiple "reasoned" or "mindful" actions in the past. Saine et al (2018) used the term "habitual inertia", suggesting it results from overvaluation of sunk costs, cognitive miserliness, and the inclination to maintaining control through constancy. Meanwhile, Jolley et al (2006) considered satisfaction with earlier behaviour to influence habitual behaviour, Status-quo satisfaction and smartwatch adoption reinforcing inertia (Nel and Boshoff, 2019); thus, habits were considered conceptually different from inertia.…”
Section: Literature Review 21 Diffusion Of Innovation Inertia and Resistance To Innovationmentioning
confidence: 99%
“…First, the stimulus can be positioned with respect to the viewer as if the viewer is using or consuming the stimulus (i.e., first person perspective) or as if somebody else does (i.e., third person perspective). The third-person imagery perspective occurs when an individual sees himself in the image from the visual perspective that an external observer would have, looking in from the outside, whereas the first-person imagery perspective occurs when the individual adopts a natural visual perspective, looking out at the situation through his own eyes [ 323 , 324 , 325 ]. Similarly, according to Saine et al [ 325 ] when people imagine themselves in various consumption scenarios, they can do so from the actor perspective (i.e., first person) or the observer perspective (i.e., third person).…”
Section: Spatial Processed Cuesmentioning
confidence: 99%
“…Saine et al [ 325 ] show that third person (vs. first-person) simulation were characterized by (1) switching to an alternative instead of staying with the status quo (default option), (2) fewer sensory components, (3) worse attitudes , and (4) a decreased willingness to pay for tempting foods. Seeing products from a third versus first perspective could also shrink perceptions of objects, such as money and time [ 326 , 327 ], possibly leading to more negative product perceptions and behavioural outcomes (FR 67).…”
Section: Spatial Processed Cuesmentioning
confidence: 99%
See 2 more Smart Citations